Silane Modification of Mesoporous Materials for the Optimization of Antiviral Drug Adsorption and Release Capabilities in Vaginal Media - Elena Whittle; Araceli Martín-Illana; Raul Cazorla-Luna; Fernando Notario-Perez; María Dolores Veiga-Ochoa; Juan Rubio; Aitana Tamayo (MDPI AG, 2021)
Three different functionalities have been incorporated into mesoporous materials by means of a coupling reaction with the siloxanes 3-glycidoxypropyl-trimethoxysilane (GLYMO), 3-methacryloxypropyl-trimethoxysilane (MEMO), and 3-mercaptopropyl-trimethoxysilane (MPTMS). The disposition of the different functional groups, as well as the interaction mechanism, with the mesoporous substrate has been identified. The amount of the antiviral drug acyclovir (ACV) adsorbed depends not only on the available surface area but also on the chemical or physicochemical interactions between functionalities. The drug adsorption isotherm of the materials functionalized with GLYMO and MPTMS follow mechanisms dependent on the different surface coverage and the possibilities to establish physicochemical interactions between the drug molecule and the functionalities. On the contrary, when functionalizing with MEMO, the dominant adsorption mechanism is characteristic of chemically bonded adsorbates. The ACV release kinetics is best fitted to the Weibull model in all the functionalized materials. When the MTPMS is used as a functionalizing agent, the drug diffusion occurs at low kinetics and homogeneously along the mesoporous channels.